Molecular simulation-based evaluation of anti-inflammatory properties of natural compounds derived from tobacco (Nicotiana tabacum L.): Computational multi-target approaches - Vinda Maharani Patricia; Aulia Fikri Hidayat; Taufik Muhammad Fakih (Pensoft Publishers, 2024)
Various components of the tobacco plant (Nicotiana tabacum L.) have undergone pharmacological assessment to highlight their traditional role in addressing different health conditions. The anti-inflammatory properties of thirteen natural substances were investigated through the use of molecular docking conducted with AutoDock 4.2.6 Tools and Molecular Dynamics Simulations (MDS) executed with GROMACS 2016.3. ADME characteristics were assessed using SwissADME (absorption, distribution, metabolism, and excretion). Chlorogenic acid and rutin, plant-derived natural compounds, showed substantial binding tendencies with cyclooxygenase-1 (COX-1), phosphodiesterase-4 (PDE4), cyclooxygenase-2 (COX-2), phosphodiesterase-7 (PDE7), interleukin-17A (IL-17A), interleukin-1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), prostaglandin E2 (PGE2), and prostaglandin F synthase. Rutin emerged as the most notable among the tested compounds (docking energy: −11.0 kcal/mol against PDE7 and prostaglandin F synthase). Chlorogenic acid also displayed substantial and noteworthy binding energies of −9.4 kcal/mol with PDE4 and PDE7 receptors. Consequently, these investigated natural compounds could potentially serve as agents that reduce inflammation and require additional in vitro and in vivo studies to aid the creation of new anti-inflammatory drugs.